Use of visual inspection with acetic acid, Pap smear, or high-risk human papillomavirus testing in women living with HIV/AIDS for posttreatment cervical cancer screening: same tests, different priorities. (14th January 2017) - Omenge Orang'o, Elkanah; Liu, Tao; Christoffersen-Deb, Astrid; Itsura, Peter; Oguda, John; Washington, Sierra; Chumba, David; Pisharodi, Latha; Cu-Uvin, Susan; Rositch, Anne F.
Abstract : Objectives: Few studies have addressed optimal follow-up for HIV-infected women after cervical treatment. This study aimed to compare performance of three available tests to detect posttreatment cervical disease in HIV-infected women in Kenya. Design: This is a prospective cohort study. Methods: At least 6 months following cryotherapy, 517 HIV-infected women were evaluated concurrently with visual inspection with acetic acid (VIA), papanicolaou (Pap) smear, and high-risk human papillomavirus (HR-HPV) testing. Women positive by any test (≥low-grade squamous intraepithelial lesion for Pap) were scheduled for colposcopy and biopsy. Among 248 with histological confirmation [and 174 assumed to be truly negative for cervical intraepithelial neoplasia (CIN)2+ after testing negative by all three tests], the ability of each test alone, or in combination, to detect CIN2+ was calculated to determine their utility in posttreatment follow-up. Results: The median age of women was 35 years, 68% were WHO stage 1–2, with a median CD4 + cell count of 410 cells/μl, and 87% were on combination antiretroviral therapy. At a median of 6.3 months posttreatment, 64% had an abnormal screen by VIA, Pap, and/or HR-HPV. Among women with histological confirmation, 72 (30%) had persistent/recurrent CIN2+. As single tests, Pap correctly classified the most cases (83%) and had the highest specificity [91% (88 and 95%); sensitivity 44% (35 and 53%)], whereas HR-HPV had the highest sensitivity [85% (75 and 96%); specificity 54% (49 and 58%)]. VIA was not sensitive [27% (18 and 36%)] for the detection of posttreatment CIN2+ [specificity 82% (79 and 86%)]. Conclusion: With the goal to minimize the number of false negatives (e.g. not miss CIN2+ posttreatment) in this population that is high-risk due to both prior cervical disease and HIV infection, HR-HPV-based algorithms are recommended. Abstract : Supplemental Digital Content is available in the text